Activation of Mammalian Unfolded Protein Response Is Compatible with the Quality Control System Operating in the Endoplasmic Reticulum - Nadanaka, Satomi (The American Society for Cell Biology, 2004)
Newly synthesized secretory and transmembrane proteins are folded and assembled in the endoplasmic reticulum (ER) where an efficient quality control system operates so that only correctly folded molecules are allowed to move along the secretory pathway. The productive folding process in the ER has been thought to be supported by the unfolded protein response (UPR), which is activated by the accumulation of unfolded proteins in the ER. However, a dilemma has emerged; activation of ATF6, a key regulator of mammalian UPR, requires intracellular transport from the ER to the Golgi apparatus. This suggests that unfolded proteins might be leaked from the ER together with ATF6 in response to ER stress, exhibiting proteotoxicity in the secretory pathway. We show here that ATF6 and correctly folded proteins are transported to the Golgi apparatus via the same route and by the same mechanism under conditions of ER stress, whereas unfolded proteins are retained in the ER. Thus, activation of the UPR is compatible with the quality control in the ER and the ER possesses a remarkable ability to select proteins to be transported in mammalian cells in marked contrast to yeast cells, which actively utilize intracellular traffic to deal with unfolded proteins accumulated in the ER.